Effects of Citrus aurantifolia Linn and Xylopia aethopica (Dunal) A. Rich Extracts on Leaf Blight Disease of Taro (Colocasia esculenta L. Schott) - F. N., Ugwuja; V.N., Offor; F.E., Akanwa; N.K., Achi; A. K., Onifade (Journal of Tropical Crop Science, 2023)
Phytophthora colocasiae Raciborski, an Oomycete phytopathogen, has been known for several decades as the causal agent of the most infectious and devastating disease of Colocasia esculenta (L.) Schott, known as taro leaf blight (TLB). Investigations were conducted in a screenhouse to determine the effects of fruit extracts of Citrus aurantifolia and Xylopia aethiopica on the incidence and severity of TLB. The experiment was set up in a completely randomized design with three replicates. Healthy taro seedlings obtained from the National Root Crops Research Institute (NRCRI), Umudike, were planted in plastic pots (5000 cm3) containing sterilized soil enriched with poultry manure. The plant extracts were applied as foliar spray on taro leaves with manually operated hand sprayer at 7 weeks after planting and continued at four days intervals for a period of 28 days. Positive check was maintained with the fungicide Ridomil (a.i. mefenoxam) applied at the rate of 0.67 mg.ml-1 while zero concentration in distilled water served as negative control. Data were subjected to one-way analysis of variance and means were separated using F-LSD. Results showed very high reduction of disease with plant extracts (P < 0.05) and Ridomil compared to the control. Citrus aurantifolia juice was more efficient in reducing the incidence and severity of TLB compared to X. aethiopica extracts and was highly significant (P< 0.05). The overwhelmingly fungitoxic effects of C. aurantifolia and X. aethiopica extracts on P. colocasiae as expressed in the reduction of disease suggests that these extracts can serve as alternative bio-fungicide for the control of TLB. Hence, further studies under field conditions are required to reestablish their efficacy.